Comparative Evaluation of VXLAN with Traditional Overlay Network Protocols - Saeed, Hasan; Askar, Shavan; Soran, Zhala; Khosnawi, Dilshad (The Indonesian Journal of Computer Science, 2024)
This article examines various network virtualization technologies, including Virtual Extensible LAN (VXLAN), as well as overlay network protocols such as VXLAN-EVPN (Ethernet VPN) and VXLAN-LISP (Locator/Identifier Separation Protocol). These protocols play a crucial role in improving the scalability and flexibility of big cloud computing infrastructures. While each of these technologies can be employed to expand a Layer 2 connection across an already established network, they possess unique qualities and applications. The objective is to offer a comprehensive comprehension of these technologies and their suitability in diverse network contexts.VXLAN-EVPN has higher performance in terms of encapsulation speed and reduced packet overhead, rendering it highly suitable for high-speed and large-scale deployments. Conversely, VXLAN-LISP demonstrates superior network latency and interoperability, offering benefits in multi-tenant and geographically distributed networks. VXLAN can be combined with other widely used overlay network protocols, including Generic Network Virtualization Encapsulation (GENEVE), Stateless Transport Tunneling (STT), and Network Virtualization using Generic Routing Encapsulation (NVGRE). The objective is to offer a comprehensive comprehension of these technologies and their suitability in diverse network contexts.